Circulating Tumour DNA Reflects Tumour Burden Independently of Adverse Events Caused by Systemic Therapies for Melanoma - Atsuko Ashida; Kaori Sakaizawa; Asuka Mikoshiba; Yukiko Kiniwa; Ryuhei Okuyama (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)